2015
DOI: 10.1094/pdis-04-14-0352-re
|View full text |Cite
|
Sign up to set email alerts
|

Tomato yellow leaf curl virus Can Overwinter in Stellaria aquatica, a Winter-Hardy TYLCV-Reservoir Weed

Abstract: S. 2015. Tomato yellow leaf curl virus can overwinter in Stellaria aquatica, a winter-hardy TYLCV-reservoir weed. Plant Dis. 99:588-592.Tomato yellow leaf curl virus (TYLCV), one of the most serious plant viruses in tropical and subtropical regions, is transmitted to host plants by the vector insect Bemisia tabaci. In order to control TYLCV, it is important to identify weed hosts for overwintering TYLCV. Stellaria aquatica, a winterhardy weed, was found growing with TYLCV-infected tomato plants in greenhouse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These results suggest that winter annual weeds play important roles in overwintering of TSWV. From our previous study on overwintering of Tomato yellow leaf curl virus (TYLCV), it has been shown that S. aquatica can act as a viral source to newly introduced insect vectors in the next cultivation after overwintering in the non-heated greenhouse (Kil et al, 2015). We did not confirm overwintering of TSWV in wintering S. aquatica plants by time-course follow-up and arti- ficial experiments shown in the previous study on TYLCV, but it can be inferred that S. aquatica plants infected with TSWV play a similar role in overwintering and spread.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that winter annual weeds play important roles in overwintering of TSWV. From our previous study on overwintering of Tomato yellow leaf curl virus (TYLCV), it has been shown that S. aquatica can act as a viral source to newly introduced insect vectors in the next cultivation after overwintering in the non-heated greenhouse (Kil et al, 2015). We did not confirm overwintering of TSWV in wintering S. aquatica plants by time-course follow-up and arti- ficial experiments shown in the previous study on TYLCV, but it can be inferred that S. aquatica plants infected with TSWV play a similar role in overwintering and spread.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm nucleotide sequences from amplicons from samples which showed positive results in previous PCR analyses, TYLCV IR was amplified by PCR with the IR-specific primer set (425 bp of target size) ( Kil et al, 2015 ). Amplicons were ligated into pGEM-T easy vectors (Promega, Madison, WI, USA) and sequenced (Macrogen, Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Whitefly-mediated TYLCV transmission from TYLCV-infected E. indica plants to healthy tomato plants was performed in restricted conditions. Non-viruliferous Bemisia tabaci (the MED cryptic species) were bred with virus-free tomato plants and virus infection was checked by PCR as described in a previous study ( Kil et al, 2015 ). E. indica plants which were inoculated with TYLCV infectious clone and confirmed as TYLCV-infected were placed in three individual BugDorm-4E4590DH cages (MegaView Science Co.) together with three-week-old healthy “Seogwang” tomato (TYLCV-susceptible cultivar) plants and non-viruliferous whiteflies at 25°C with a day length of 12 h. A negative control group was also set with TYLCV-free E. indica , non-viruliferous whiteflies and healthy tomatoes in an insect cage.…”
Section: Methodsmentioning
confidence: 99%
“…Among the weed hosts for ToCV identified in this study, P. americana is a perennial weed and should be completely removed from inside or around tomato greenhouses to eliminate the continuous presence of ToCV. In our previous weed host survey of TYLCV, we identified and experimentally proved that Myosoton aquaticum, a perennial weed, could be a main TYLCV reservoir weed near tomato greenhouses and a source of consecutive TYLCV infections (Kil et al 2015). Non-viruliferous whitefly transmitted TYLCV from over-wintered TYLCV-infected M. aquaticum in spring and viruliferous whitefly transmitted the TYLCV to new tomato plants.…”
mentioning
confidence: 93%